CARDIAC TAMPONADE IN MYXEDEMA CRISIS – AN UNCOMMON PRESENTATION OF A RARE ENDOCRINE EMERGENCY - Kwek, Kevin; Lai, Ray; Lee, Shaun; Seow, Cherng Jye; Quek, Timothy (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Myxedema crisis is a state of severe hyperthyroidism with end-organ decompensation. Pericardial effusion is an uncommon manifestation of hypothyroidism. As large effusions are rare and typically accumulate slowly, cardiac tamponade rarely occurs. We present a rare case of cardiac tamponade from a large pericardial effusion in a patient with myxedema crisis. CASE Our patient was referred to our Endocrinology service for evaluation of severe hypothyroidism. A diagnosis of myxedema crisis was made due to the presence of biochemically-proven severe hypothyroidism fT4 2.0 pmol/L [normal range (NR) 8-16], fT3 <2 pmol/L (NR 3.5- 6), and TSH 82.27 mIU/L (NR 0.45-4.5), with features of end-organ decompensation (congestive heart failure, hypotension, bradycardia, and altered mental status). Transthoracic echocardiography revealed a large pericardial effusion with small ventricular size and reduced tricuspid inflow velocity suggestive of a partially compensated tamponade. The patient received an intravenous thyroxine loading dose of 200 mcg followed by 100mcg daily maintenance doses. Despite improvement of the manifestations of hypothyroidism and normalisation of serum thyroxine levels, she remained persistently hypoxemic and could not be weaned from supplemental oxygen. Hence, bedside pericardiocentesis was performed with diagnostic and therapeutic intent. Pericardial fluid analysis did not reveal any secondary cause. She demonstrated good clinical improvement post-pericardiocentesis and was eventually discharged. CONCLUSION Cardiac tamponade is a life-threatening severe manifestation of myxedema crisis. As pericardiocentesis may be lifesaving, we recommend screening for cardiac tamponade in patients with myxedema crisis who demonstrate poor cardiorespiratory improvement despite adequate thyroid hormone therapy.